Principles of addiction medicine : the essentials - Cavacuiti, Chris. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Principles of Addiction Medicine: The Essentials is a compact and portable distillation of the American Society of Addiction Medicine's flagship text, Principles of Addiction Medicine. This handbook present the clinically essential points from the larger text in an easy-to-follow outlined and bulleted format. Each chapter follows a template with structured headings such as pharmacokinetics, pharmacodynamics, therapeutic uses, effects, liability, and withdrawal. Principles of Addiction Medicine: The Essentials is an excellent reference for a wide variety of addiction medicine professionals, including psychiatrists, psychologists, psychiatric nurses, social workers, internal medicine/primary care physicians, and substance abuse counselors"--Provided by publisher.